HUBUNGAN MEDIA PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR BIDANG STUDI SEJARAH SISWA SMA NEGERI 3 LUMAJANG - Joni Joni (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2015)
This research aimed to know the correlation between instructional media and learning motivation toward learning achievement, Indonesian history subject, of senior high students at SMA Negeri 3 Lumajang. The respondents were ninety (90) students. As the result, it showed that instructional media and learning motivation positively influenced students learning achievement.